How libraries can enhance customer service by implementing a customer value mindset. Issue 1 (21st December 2016) - Weinstein, Art T.; McFarlane, Donovan A.
Abstract : Libraries have a rich tradition of solid customer service. Good service today, however, is often not good enough. Libraries can improve the customer experience by understanding what it means to truly deliver outstanding value. Implementing customer‐centric marketing and the latest technology can increase the perceived value of library usage before, during, and after service delivery. The evolving library experience framework explains how library administrators can prepare for current challenges and future changes to enhance customer service. A customer value‐based services perspective will help libraries strengthen overall user experiences to keep a larger "share of customer" from formidable information rivals such as search engines, online databases, news sources, video sharing sites, internet service providers, and content creators.